Men's attitude towards wife-beating: understanding the pattern and trend in India - Manas Ranjan Pradhan; Prasenjit De (BMC, 2024)
Abstract Background Intimate partner violence (IPV) is a severe human rights violation and a global burden on public health. Wife-beating is a form of IPV and an extension of the patriarchal philosophy that legitimizes men's control over their spouses. This study investigates (a) the trends and patterns of men's attitudes towards justification of wife-beating and (b) the socio-demographic factors associated with changes in men's attitudes towards wife-beating between 2005-06 and 2019-21 in India. Methods The present study utilized data from the last three rounds of the National Family Health Survey (NFHS): NFHS-3 (2005-06), NFHS-4 (2015-16), and NFHS-5 (2019-21) with a total sample of 2,76,672 men aged 15-54. The primary outcome variable was men's attitudes toward wife-beating. Attitude towards the household and the sexual autonomy of the wife were the two key predictors, in addition to other structural factors. Descriptive, bivariate, and multivariate logistic regression analyses were performed on weighted data using Stata. Hosmer-Lemeshow test, Classification table, and ROC curve were carried out to enhance the robustness of the analysis and validity of the model. Results In 2005-06, 50% of men justified wife-beating in at least one of the seven contexts, which reduced to 42% in 2015-16 and then marginally increased to 44% in 2019-21. Men with an authoritarian attitude toward household autonomy (AOR: 2.34; CI: 2.30,2.38) and sexual autonomy of the wife (AOR: 1.68; CI: 1.65,1.71) were more likely to justify wife-beating than their egalitarian counterparts. Inadequate education, younger age, family history of IPV, alcohol consumption, poverty, and rural settings are associated with an elevated risk of abusive attitudes towards wife-beating. Conclusion A sizable percentage of men, more so those socio-economically marginalized, continue to justify wife-beating, albeit with considerable decline over the years. The findings suggest customized policies and programs enhancing gender egalitarian norms among young men, more opportunities to pursue higher education, alleviating poverty through employment opportunities, and raising awareness about domestic violence in rural settings would help develop more egalitarian gender norms and attitudes towards wife-beating.